2017
DOI: 10.1590/1517-869220172306170049
|View full text |Cite
|
Sign up to set email alerts
|

Atletas De Taekwondo Têm Melhor Controle Postural Do Que Atletas De Handebol E Futebol Americano

Abstract: Introdução: O controle postural é um pré-requisito importante para o desempenho do atleta no esporte. Além disso, o sistema de controle postural contribui para a prevenção de lesões. Déficits nesse sistema podem levar a instabilidade corporal e sobrecarga das estruturas musculoesqueléticas, gerando disfunção e dor. Objetivos: A proposta deste estudo foi avaliar o controle postural em três diferentes modalidades esportivas: taekwondo, handebol e futebol americano. Métodos: Todos os atletas executaram o teste de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
1
4
0
1
Order By: Relevance
“…In previous studies, including one from our research team, 26 the one-legged stance task was a sufficient challenge to discriminate postural instability between different sports modalities and training experience, such as taekwondo, handball, American football, soccer, and nonathletes, 14,26,27 which supports the use of this condition in the present study. However, no study has investigated the effects of knee posture at 30°of flexion on postural control based on COP parameters in athletes with CLBP, which in turn, adds a challenge to the discussion of our findings.…”
Section: Knee Position Differences On Postural Controlsupporting
confidence: 75%
See 1 more Smart Citation
“…In previous studies, including one from our research team, 26 the one-legged stance task was a sufficient challenge to discriminate postural instability between different sports modalities and training experience, such as taekwondo, handball, American football, soccer, and nonathletes, 14,26,27 which supports the use of this condition in the present study. However, no study has investigated the effects of knee posture at 30°of flexion on postural control based on COP parameters in athletes with CLBP, which in turn, adds a challenge to the discussion of our findings.…”
Section: Knee Position Differences On Postural Controlsupporting
confidence: 75%
“…In fact, the one-legged stance with knee extension has been examined in previous studies, including those athletes with CLBP. 7,14,[24][25][26][27] However, knee extension constitutes a locking mechanism, a kinematic phenomenon also known as the screw home that increases knee stability 28 ; contrary, the knee flexion position above 20°constitutes a position frequently adopted during most sports where the screw home mechanism is absent. At this knee position, the individual can present an articular mobility with signs of joint instability 28 and, consequently, increase their chances to have lumbar or lower-limb instability and back injury.…”
mentioning
confidence: 99%
“…In addition, sports training can increase the ability to use somatosensory information, also resulting in improved postural balance. 10,11 The study by Heleno et al 12 showed that a five-week sensory-motor training program, with static and dynamic exercises associated with soccer movements, improved the functional performance and postural control of young soccer players. These findings corroborate the evidence that the practice of sports activities can increase physical fitness and decrease the fatigue parameters that are critical for postural balance.…”
Section: Resultsmentioning
confidence: 99%
“…The authors report that for taekwondo the center of gravity of the right foot corresponds on average to 600 mm 2 , while for the left it corresponds on average to 700 mm 2 ; for Handball, the center of gravity of the right foot corresponds on average to 1100 mm 2 , while for the left it corresponds to an average of 1100 mm 2 and for American football the center of gravity of the right foot corresponds to an average of 1100 mm 2 , while for the left it corresponds to average at 1100 mm 2 ; In the present study, a better stabilometric performance is observed in the areas of the right center of gravity, with a record of 55 mm 2 on average and for the left foot of 21 mm 2 . These results are due to greater motor control at the stabilometric level given by constantly working on the unstable base represented by the skateboard, the duration of sports practice per day and the dynamics of the sport [20].…”
Section: Discussionmentioning
confidence: 99%